The Prevalence of Latent Tuberculosis Infection and Smear Positive Pulmonary Tuberculosis in People with Household Close Contact with Tuberculosis in North of Iran - Moosazadeh, Mahmood (Iran J Med Sci, 2015)
One of the recommended strategies for preventing tuberculosis is to screen high-risk populations with respect to Mycobacterium tuberculosis (TB) infection. The aim of the present study was to investigate latent infection and active tuberculosis in people with close household contact. It was a cross-sectional descriptive, analytical study with the sample size of 668 people from homes with one infected resident. In order to diagnose tuberculosis latent infection, the PPD test was done. To determine patients with smear-positive pulmonary tuberculosis, three sputum samples were taken from every patient and were examined using direct microscopy and culture. Data was analyzed by SPSS20 software. The prevalence of latent tuberculosis infection and smear-positive pulmonary tuberculosis were 42.8% and 0.9% respectively. The prevalence of latent tuberculosis infection and smear-positive pulmonary tuberculosis in people with close household contact were less than that of other studies. However, smear-positive pulmonary tuberculosis in people with close household contact was 199.5 times more than that of the general population.